Optimal Credit Policy Selection: A Dynamic Approach - Mehta, Dileep (Journal of Financial and Quantitative Analysis, 1970)
In an earlier paper [2], the sequential decision process was applied to two major facets of credit management: (a) deriving unambiguous decision rules for handling individual credit requests; and (b) devising relevant credit indices for effective management control and evaluation of the system. Usefulness of the model was constrained by its static nature and by exogenous determination of other significant variables, notably, collection efforts and costs.